LIQUEFACTION POTENTIAL ANALYSIS BASED ON DOWNHOLE SEISMIC DATA IN SEPAKU DISTRICT, NORTH PENAJAM PASER REGENCY, EAST KALIMANTAN - Devandra, Muhammad
Liquefaction is a complex phenomenon in which there are various parameters to analyze the potential for this phenomenon. In this study, the S wave velocity is a parameter used to analyze the potential for liquefaction because this seismic wave parameter is quite sensitive to the phenomenon of liquefaction. One of the methods that can be used to determine S wave velocity is downhole seismic. The downhole seismic was tested in the Pamaluan Formation in the Sepaku District, which is composed of claystone and shale with inserts of marl, sandstone, and limestone. The downhole seismic has four interpretation methods to obtain the value of S wave velocity, one of them was the refracted ray-path method, which applies the Snell’s Law when passing through layer boundaries. The calculated S wave velocity is then used to determine the value of the Cyclic Resistance Ratio (CRR) with the VS1 – CRR relationship. This CRR value will be compared with the Cyclic Stress Ratio (CSR) to determine the Factor of Safety (FS) value in each depth of the study area. The FS value can be used to see whether the depth has the liquefaction potential or not. Furthermore, this study also accommodates simulations of groundwater level because the groundwater level plays a substantial role as the trigger for liquefaction events. The result of this study shows that Sepaku District has the potential for liquefaction at 0 – 3 m depth if the earthquake strength is on a scale of MW 5 and 5.5, at 0 – 5 m depth if the earthquake strength is on a scale of MW 6 and 6.5, and at 0 – 6 m depth if the earthquake strength is on a scale of MW 7 with a groundwater level of less than 1 m.